Pelatihan Tenaga Pendidik dan Tenaga Kependidikan dalam Pengelolaan Administrasi Melalui E-Workshop - Rosita, Yesy Diah; Makhfuddin Akbar, Ronny; Indra Kurniawan, Fajar; Rudiyanto, M. Adik (ABDIMAS NUSANTARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The competence of the community, especially educators and educational staff in data processing can influence a decision-maker's decision to set academic policies. Solid working hours limit them to try to improve their competence. The types of competencies needed by the community are different. Therefore, market analysis is required by publishing a training offer with a choice of types of competencies and the time of implementation of activities as needed. The training offered is online-based or can be called an e-workshop due to the limited time of educators and education staff. In addition, the purpose of the activity is to provide training and assistance to communities outside Mojokerto Regency. The results of E-workshop registration show that participants need competency in data processing with MS. Word and MS. Excel. Based on the participants' participation in 10 meetings with various sessions and 4 resource persons who provided materials that support their profession, the enthusiasm level of the participants can be said to be more than 70% so that it can be said that E-workshop-based training has quite good benefits for participants who have limited time.